Pengaruh Zeolit Alam Terhadap Kadar Fe-larut dan Al-dd Pada Tanah Sulfat Masam di Desa Sungai Rangas Kecamatan Martapura Barat Kabupaten Banjar - Timur Priono; Syaifuddin Syaifuddin; Salamiah Salamiah (Agroekotek View, 2018)
Problems of acidity and heavy metal levels in tidal land can be improved by using ameliorant one of them natural zeolite. Based on ability to exchange ions and improvements in chemical properties of the soil. Klaten natural zeolite of Yogyakarta contains 29.4% mordenite with size 500 nm -20 nm.This research using (RAL) one factor with 5 treatment, 4 replication and 20 unit experiment. The treatment consists of a). Control (0 ton.ha-1) b). 2.5 ton.ha-1 c). 5 ton.ha-1 d). 7.5 ton.ha-1 and e). 10 ton.ha-1 natural zeolite. Treatment 10 ton.ha-1 natural zeolite can decrease Fe2+ to 15.90 ppm and Al-dd to 1.07 me. 100 g-1 on soil.